2012
DOI: 10.7448/ias.15.4.17991
|View full text |Cite
|
Sign up to set email alerts
|

Community voices: barriers and opportunities for programmes to successfully prevent vertical transmission of HIV identified through consultations among people living with HIV

Abstract: IntroductionIn 2010, two global networks of people living with HIV, the International Community of Women Living with HIV (ICW Global) and the Global Network of People living with HIV (GNP + ) were invited to review a draft strategic framework for the global scale up of prevention of vertical transmission (PVT) through the primary prevention of HIV and the prevention of unintended pregnancies among women living with HIV. In order to ensure recommendations were based on expressed needs of people living with HIV,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…All the participants said that the counselling was mainly provided during pregnancy period when women were attending the ANC visits. The finding of this study is consistent with the results from other studies conducted in developing countries [30] [31], including South Africa [32]. For example, Anderson et al's findings reported existence of postnatal counselling gaps in Jamaica [31].…”
Section: Health Service Perception Barrierssupporting
confidence: 92%
See 1 more Smart Citation
“…All the participants said that the counselling was mainly provided during pregnancy period when women were attending the ANC visits. The finding of this study is consistent with the results from other studies conducted in developing countries [30] [31], including South Africa [32]. For example, Anderson et al's findings reported existence of postnatal counselling gaps in Jamaica [31].…”
Section: Health Service Perception Barrierssupporting
confidence: 92%
“…For example, Anderson et al's findings reported existence of postnatal counselling gaps in Jamaica [31]. In Uganda, Larsson et al's study found inadequate postnatal PMTCT counseling [30]. Similarly, Chopra et al's study reported the poor quality of the postnatal PMTCT counselling in South Africa [32].…”
Section: Health Service Perception Barriersmentioning
confidence: 99%
“…Similar to this study, a review conducted in Africa found that patients want a better understanding of their medications and that stigma may prevent access to information (Patel & Dowse, 2013). Other studies pertaining to HIV also found that information regarding healthy lifestyles, emotional health, or general wellness issues would be useful to patients (Anderson et al, 2012; Huber & Cruz, 2000; Julien & Fourie, 2015). Across the international literature, patients identified different sources of information but generally indicated that providers are either the best sources or one of the biggest barriers to effective information exchange.…”
Section: Discussionmentioning
confidence: 99%
“…Segregated health care can feel jarring to the HIVaffected couple (Anderson et al, 2012;Beckerman, 2002;Davis & Flowers, 2011;Gamarel et al, 2014;Persson, 2008Persson, , 2013Remien, Carballo-Dieguez, & Wagner, 1995). In Perrson's qualitative study of 20 couples, HIV-negative partners described their experience with health care as problematic.…”
Section: Introductionmentioning
confidence: 93%